Assessing the Role of Demographic Variables on Employer Branding. - Kashive, Neerja; Khanna, Vandana Tandon (Advances in Social Sciences Research Journal, 2018)
This paper studies the influence of demographic variables like age, gender, qualification and work experience for the impact of early recruitment activities (ERA) and employer brand knowledge (EBK) on Organization attractiveness (OA) and Firm Performance (FP).The questionnaire was administered on 750 final year students of MBA, MCA and BE. The companies were chosen on the basis of NASSCOM top 20 IT-BPM employers in India 2015-16.It was observed that early recruitment activities (ERA) have significance negative impact and Employer Brand Knowledge (EBK) have significance positive impact on Organization attractiveness (OA) for both the age groups and both the genders, for only MBA students and with nil and 1-2 years of experience. While only Employer Brand Knowledge (EBK) have significance impact on Firm Performance (FP) for both the age groups and both the genders and nil level of experience. When designing the advertisement and publicity campaign, the employer need to be very careful as it can lead to negative effect on attractiveness of organization. They should focus more on developing employer brand knowledge with respect to brand awareness, reputation and image. The originality of the review is its uniqueness in showing how different demographic can play important role in deciding the employer brand strategies for any organization which can help in focusing the right target groups for employer brand building.